Epidemiology of Corneal Neovascularization and Its Impact on Visual Acuity and Sensitivity: A 14-Year Retrospective Study - Lasagni Vitar, Romina Mayra; Triolo, Giacinto; Fonteyne, Philippe; Acuti Martellucci, Cecilia; Manzoli, Lamberto; Rama, Paolo; Ferrari, Giulio (Frontiers in Medicine, 2021)
Purpose: To quantify the severity and location of corneal neovascularization (cNV) and its impact on visual acuity and corneal sensitivity in a cohort of patients referred to a specialist cornea clinic. To describe the etiology of cNV in the cohort. Methods: We retrospectively evaluated the charts of 13,493 subjects referred to the San Raffaele Cornea Unit between January 2004 and December 2018 to search for cNV diagnosis. Corneal neovascularization severity was measured in quadrants (range: 1-4), location was defined as superficial, deep, or both. Best spectacle corrected visual acuity (BSCVA) was measured in logMar. We used multiple regression analysis to identify independent predictors of logMAR, after adjusting for age, gender, keratoconus, herpes keratitis, penetrating keratoplasty, trauma, and cataract surgery. Results: cNV was diagnosed in 10.4% of the patients analyzed. The most prevalent etiology of cNV in our population was non-infectious corneal dystrophies/degenerations, followed by herpes simplex virus infection. cNV affected OD, OS, or both eyes in 35.6%, 40.2% and 24.2% of cases, respectively. Mean BSCVA (SD) was 0.59 (0.76), 0.74 (0.94) and 1.24 (1.08) in cNV 1, 2 and 3-4 quadrants group. Superficial, deep, or mixed cNV occurred in 1029, 348 and 205 eyes. Severe cNV (3-4 quadrants) was a significant predictor of low visual acuity (p<0.001) and reduced corneal sensitivity (p<0.05). cNV location and its severity were associated (p<0.05). In addition, corneal anesthesia was associated with lower BSCVA (p<0.001). Conclusion: Severe and deep cNV are associated with reduced visual acuity and corneal sensitivity. Our data strongly support the relevance of appropriate follow-up, as cNV is a major risk factor for graft rejection.